Study Of Needed Conditions To Recover The Metal Elements From Spent Lead-Acid Batteries By Hydromettalurgical Method - غنام نزار; حيدر مضر (Latakia University Journal -Basic Sciences Series, 2020)
In this research, we study the operation of recovering Pb from spent Lead-Acid Batteries. The operation is done with Hydrometallurgy by deposition in the form of Sulphides depending on the values of Ksp of the studied elements components. the dismantling and cutting operations were done by electrical saw, then separate the components. The study of recovery Lead from its compounds in the batteries which are (Pb-PbO-PbO2-PbSO4) is done by using HNO3 (2N) we recovered Lead in the poles, the nets and the grids, Then to increase the output we used pure Citric Acid and treated the lead components with Ammonium sulphide so Lead Sulfide (PbS) is precipitate. After that operations to treat the remaining lead compounds were done by using only pure Citric Acid. After complete dissolution, the operation of precipitate was done also with Ammonium sulphide and we had the Lead Sulfide (PbS) as a final product. This study has an environmental importance of disposing of battery wastes and economical by obtaining lead element in addition to plastic as a by-product.